Paul Maenz Köln 1970-1975. - Paul Maenz, Köln (Köln : Paul Maenz, 1975)
Acconci, Vito ; Albers, Josef ; Andre, Carl ; de Andrea, John ; Art & Language ; Asher, Michael ; Askevold, David ; Atkinson, Terry ; Bainbridge, David ; Baldessari, John ; Baldwin, Michael ; Barry, Robert ; Barthes, Roland ; Becher, Bernd & Hilla ; Ben ; Benjamin, Walter ; Bertholin, Jean-Marie ; Beuys, Joseph ; Bill, Max ; Bochnig, Heidi ; Boyle, Mark ; Brecht, Bert ; Burchartz, Max ; Burden, Chris ; Buren, Daniel ; Burgin, Victor ; Burn, Ian ; Burri, Alberto ; Cabanne, Pierre ; Cage, John ; Cassirer, Ernst ; Castellani, Enrico ; Celant, Germano ; Charlesworth, Sarah ; Charlton, Alan ; Close, Chuck ; Darboven, Hanne ; Dexel, Walter ; Dibbets, Jan ; van Doesburg, Theo ; Dolla, Noël ; Dorazio, Piero ; Duchamp, Marcel ; Dutschke, Rudi ; Fautrier, Jean ; Feldmann, Hans-Peter ; Fischer, Konrad ; Flanagan, Barry ; Riverhead (New York) ; Fontana, Lucio ; Fulton, Hamish ; Gide, André ; Griffa, Giorgio ; Haacke, Hans ; Hanson, Duane ; Harrison, Charles ; Heizer, Michael ; Hills, Joan ; Hintze, Otto ; Hofmann, Werner ; Huebler, Douglas ; Insley, Will ; Irwin, Robert ; Johns, Jasper ; Judd, Donald ; Kaprow, Allan ; Kawara, On ; Kelly, Ellsworth ; Klein, Yves ; Kline, Franz ; Knoebel, Imi ; Knorr, Anneliese & Ernst ; de Kooning, Willem ; Kosuth, Joseph ; Kounellis, Jannis ; Kozlov, Christine ; Krahmer, Christine ; Lévy-Strauss, Claude ; LeWitt, Sol ; Lichtenstein, Roy ; Lissitzky, El ; Lohse, Richard Paul ; Long, Richard ; Louw, Roelof ; Lueg, Konrad ; Lüthi, Urs ; Maenz, Paul ; Maloney, Martin ; Mangold, Robert ; Manzoni, Piero ; Marcuse, Herbert ; Marden, Brice ; de Maria, Walter ; Martin, Agnes ; McLuhan, Marshall ; Merleau-Ponty, Maurice ; Metken, Günter ; Michals, Duane ; Mields, Rune ; Morris, Lynda ; Morris, Robert ; Nauman, Bruce ; Newman, Barnett ; etc.
Duits
boek